2021
DOI: 10.1186/s12879-021-05781-w
|View full text |Cite|
|
Sign up to set email alerts
|

Acute cardiovascular events in patients with community acquired pneumonia: results from the observational prospective FADOI-ICECAP study

Abstract: Background The burden of cardiovascular (CV) complications in patients hospitalised for community-acquired pneumonia (CAP) is still uncertain. Available studies used different designs and different criteria to define CV complications. We assessed the cumulative incidence of acute of CV complications during hospitalisation for CAP in Internal Medicine Units (IMUs). Methods This was a prospective study carried out in 26 IMUs, enrolling patients conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 27 publications
0
15
1
5
Order By: Relevance
“…However, the incidence of CVEs differs as the different inclusion criteria of CVEs. In a multicenter prospective study enrolled 1266 patients with CAP, data indicated that 23.8% of patients experienced at least a CV event (excluded the thromboembolic diseases), 12 higher than that in our study. We considered the gap is mainly related to the low proportion of patients in PSI class IV or V or CURB-65 class 3–5.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…However, the incidence of CVEs differs as the different inclusion criteria of CVEs. In a multicenter prospective study enrolled 1266 patients with CAP, data indicated that 23.8% of patients experienced at least a CV event (excluded the thromboembolic diseases), 12 higher than that in our study. We considered the gap is mainly related to the low proportion of patients in PSI class IV or V or CURB-65 class 3–5.…”
Section: Discussioncontrasting
confidence: 67%
“…We confirmed previous reports showing that history of heart failure, previously diagnosed coronary artery disease, pleural effusion, multilobe infiltration, age and BUN were independently associated with CVEs. 12 , 16 , 23–26 In the first analysis of prospectively collected data from the Pneumonia Patient Outcomes Team cohort study in patients with CAP, sodium<130 mmol/L was considered as independent risk factor for incident cardiac complications. 25 In our data, level of blood sodium (OR 0.98; 95% CI, 0.97–0.99, p =0.007) was protective factor for the occurrence of CVEs, suggesting the similar conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of pneumonia-associated cardiovascular complications included hypoxia, proinflammatory status, platelet activation, thrombosis formation, unstable plaque, increased sympathetic tone, and several adverse effects of antibiotics [ 11 , 17 , 18 , 19 ]. As most of the MACEs were due to thromboembolic events, we investigated the CHA2DS2-VASc score to predict MACE.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that approximately 10–15% of patients developed heart failure after pneumonia infection [ 6 , 17 ]. Although the mechanism is unclear, several hypotheses have been proposed, including persistent inflammatory state, hypoxia, tachycardia, specific microbacteria, and fluid overload during the management of pneumonia infection [ 4 , 10 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation